Dinamika Kebijakan Kurikulum Pendidikan di Indonesia Pasca Reformasi - Dilla Janu Istanti (Fakultas Ilmu Sosial dan Ilmu Politik, 2019)
The dynamics curriculum policy in indonesia often changed. A policy change often without direction and substance clear and measurable. After reform, education curriculum has been modified several changes, KBK curriculum in 2004 who changed to KTSP curriculum in 2006. Curriculum KTSP then turned into curriculum 13 to 2018 discourse national curriculum. This shows the curriculum change education is the unstable dynamics. A policy change often occurs every time there was a regime change. A policy change often lose significance of these itself as a means of solving a problem to do that would be more proactive, adaptive, and interpretive. This often said that the policies only into a hegemoni to keep power seen in this portrait. This essay will try to looked at how the dynamics a policy change in education curriculum in Indonesia following reform.